Mayarhynchus karlae n. g., n. sp. (Acanthocephala: Neoechinorhynchidae), a parasite of cichlids (Perciformes: Cichlidae) in southeastern Mexico, with comments on the paraphyly of Neoechynorhynchus Stiles & Hassall, 1905 - Pinacho Pinacho, Carlos D. (2017)
Mayarhynchus n. g. (Acanthocephala: Neoechinorhynchidae) is erected for Mayarhynchus karlae n. g, n. sp. described from the intestine of four species of cichlid fishes distributed from southeastern Mexico. The new genus placed in the family Neoechinorhynchidae (Ward, 1917) Van Cleave, 1928, is readily distinguished from the other 17 genera in the family by having a small proboscis armed with 45–46 relatively weak rooted hooks arranged in nine longitudinal rows of five hooks each. In addition, Mayarhynchus n. g., n. sp. is diagnosed by the presence of a short trunk, body wall with five dorsal and one ventral giant hypodermal nuclei, proboscis receptacle nearly cylindrical with single layered wall, lemnisci broad and flat with large nuclei, testes in tandem, cement gland with eight large nuclei, and eggs elongate to oval. Partial sequences of the cytochrome c oxidase subunit 1 (cox1), internal transcribed spacers (ITS1 + 5.8S + ITS2), and the D2-D3 domains of the large subunit rRNA gene (28S) were obtained for five specimens of the new species and other species belonging to the Neoechinorhynchidae. Phylogenetic analyses confirmed that the new genus belongs to the Neoechynorhynchidae and indicated that the genus Neoechynorhynchus Stiles & Hassall, 1905 is not monophyletic. Comparison between three populations of the new species yielded nine variable sites for cox1, 11 for ITS and four for 28S.